Update on the Regulation of HIPK1, HIPK2 and HIPK3 Protein Kinases by microRNAs - Conte, Andrea; Pierantoni, Giovanna M. (MicroRNA, 2018)
The Homeodomain-Interacting Protein Kinases (HIPKs) HIPK1, HIPK2 and HIPK3 are Ser/Thr kinases which interact with homeobox proteins and other transcription factors, acting as transcriptional coactivators or corepressors. HIPKs contribute to regulate several biological processes, such as signal transduction, apoptosis, embryonic development, DNA-damage response, and cellular proliferation, in response to various extracellular stimuli. Recently it has emerged that, in addition to their role in cancer, fibrosis and diabetes, HIPKs may also be involved in other human diseases, including Amyotrophic Lateral Sclerosis (ALS), Rett syndrome, cerebellar diseases, and retinal vascular dysfunction. Methods: Here, we update our previous paper concerning the regulation of HIPK proteins expression by microRNAs (miRNAs), pointing out the most recent findings about new cellular mechanisms and diseases which are affected by the interplay between HIPKs and miRNAs. Conclusion: Recently, it has emerged that HIPKs and their related miRNAs are involved in diabetic nephropathy, gastric cancer chemoresistance, cervical cancer progression, and recombinant protein expression in cultured cells. Interestingly, circular RNAs (circRNAs) deriving from HIPK2 and HIPK3 loci also modulate cellular proliferation and viability by sponging several miRNAs, thus emerging as new putative therapeutic targets for diabetes-associated retinal vascular dysfunction, astrogliosis and cancer.
Keywords: miRNA